2015
DOI: 10.1080/15384047.2015.1017691
|View full text |Cite|
|
Sign up to set email alerts
|

HMGB1-mediated autophagy modulates sensitivity of colorectal cancer cells to oxaliplatin via MEK/ERK signaling pathway

Abstract: In the present study, we examined the mechanisms of oxaliplatin-induced drug resistance in human colorectal cancer cell lines HT29 and HCT116. Our results demonstrate a significant autophagy expression in CRC cells after an oxaliplatin treatment. Administration of oxaliplatin to human CRC cells significantly enhanced the expression of HMGB1, which regulated the autophagy response and negatively regulate the cell apoptosis. Moreover, a decreased oxaliplatin -induced autophagy response and an increased apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 28 publications
4
64
1
Order By: Relevance
“…Thus, the induction of autophagy has an important role in gemcitabine resistance of HIPC cells. Consistently, it has been reported that induced autophagy modulates sensitivity of colorectal cancer cells to oxaliplatin (19) and mediates multi-drug resistance in osteosarcoma (20).…”
Section: Discussionsupporting
confidence: 51%
“…Thus, the induction of autophagy has an important role in gemcitabine resistance of HIPC cells. Consistently, it has been reported that induced autophagy modulates sensitivity of colorectal cancer cells to oxaliplatin (19) and mediates multi-drug resistance in osteosarcoma (20).…”
Section: Discussionsupporting
confidence: 51%
“…Additionally, HMGB proteins are subdivided into HMGB1, HMGB2, and HMGB3, all of which contain two HMG-box domains and a highly acidic Cterminal tail [10,11]. The current study found the expression levels of HMGB1 gene were significantly higher than that of the corresponding normal tissues in a variety of tumor tissues, including colorectal cancer, breast cancer, pancreatic cancer, melanoma, et al, which suggested that HMGB1 was involved in the occurrence and development of tumors [12][13][14][15][16]. Dong found that knockdown of the HMGB1 expression inhibited tumor growth and metastasis in human liver cancer through AKT-mediated regulation of Ki-67 and MMP-2 expression [17].…”
Section: Introductionmentioning
confidence: 42%
“…Chen had reported that HMGB1 was a novel biomarker and a therapeutic target for human ovarian cancer, which was associated with poor clinicopathologic features [19]. Liu et al had studied oxaliplatininduced drug resistance in human colorectal cancer cell lines HT29 and HCT116, and they found HMGB1-mediated autophagy modulated sensitivity of colorectal cancer cells to oxaliplatin via MEK/ERK signaling pathway [12]. Meanwhile, HMGB1, as one of the mediators in inflammatory reaction, was associated with tumorigenesis.…”
Section: Introductionmentioning
confidence: 97%
“…3 In fact, the exact underlying molecular mechanism responsible for L-OHP resistance remains elusive up to now. Resistance to L-OHP is a complex process and several signaling pathways, such as the nuclear factor-kappa B (NF-κB) pathway, 4 the extracellular signal-regulated kinase (ERK)/Extracellular signal-regulated kinase (MEK) pathway, 5 and the protein kinase B (AKT/PKB) pathway, 6 have been involved in this phenomenon. Accumulating evidences demonstrate that activation of the AKT signaling pathway always leads to resistance to L-OHP induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%